Mathematical modeling of heat and mass transfer at underground coal gasification - Aleksandr Subbotin; Roman Kulesh; Anna Mazanik (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
Relevance of the work is caused by the need of developing a mathematical model of thermal processes occurring at underground coal seams gasification as a tool to assess the possibilities and conditions of gasification. The main aim of the study is to develop and to test a mathematical model applied to the underground gasification of coal beds as unconventional way of their development. The methods used in the study: numerical solution of boundary value problems using iterative-interpolation method. Results: The authors have stated mathematical model describing heat and mass transfer in underground coal gasification. Numerical studies allow us to determine the composition of the resulting gas, depending on the temperature, pressure and composition of gasification products of s blown hot gas. The dependences of the combustible gas component output on concentration of injected oxidant: dry air, mixture of oxygen, nitrogen and water vapor in different proportions. As a result of numerical calculations it was found out that at underground coal gasification oxygen or vapor-air mixture fed to a coal bed is almost completely consumed in the region of pyrolysis products oxidation; the rest part of coal volume contains slight amount of oxidant. Therefore, in a coke layer the maximum mass concentration of combustible gas accumulates. The gas is transferred by moving gaseous oxidation products from oxidation area to the environment. It was shown that when changing oxygen and steam concentration in the vapor-air mixture fed to the coal bed it is possible to change significantly the composition of the resulting combustible gas and to reduce non-combustible gas fraction (carbon dioxide). Carbon dioxide concentration can be reduced increasing gasification temperature which is 800 K in the study. Pressure increase in oxidizer results in growth of combustible gas concentration, but this effect is less significant hence. Therefore the combustible gas concentration in gasification products depends largely on water vapor concentration, the gasification temperature and oxygen concentration in vapor-air mixture fed into the coal bed.